Adhunik Bharatiya Bhasaharuma Avikartatmak Samrachanako Isthiti - Aryal, Balram (Tribhuvan University Journal, 2010)
Not available. Key words: Avikartatmak Samrachanako Isthiti Tribhuvan University Journal Volume XVI, 1993 Page: 120-132 Uploaded date: 4 October, 2010